2022
DOI: 10.1007/s10212-022-00605-0
|View full text |Cite
|
Sign up to set email alerts
|

Different associations of parental involvement with children’s learning of Chinese, English, and math: a three-wave longitudinal study

Abstract: Due to the impact of COVID-19, children and their parents are spending more time at home, which increases parent-child interactions. The goals of the present study were to examine the mediating effects of children's learning engagement on the relationships of parental involvement in Chinese, English, and math performance and to investigate whether parent-perceived parental involvement and child-perceived parental involvement consistently affected children's academic performance. Data were collected from 253 Ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…More teachers' guidance and training would have been needed. Using data on Chinese primary school students during Covid-19, Wang et al (2022) concluded that parental involvement had a positive impact on children's achievement in Chinese and English, but not in math. While parents are likely to be knowledgeable about the learning content of Chinese and English lessons, this may not be the case for math lessons.…”
Section: Methodsmentioning
confidence: 99%
“…More teachers' guidance and training would have been needed. Using data on Chinese primary school students during Covid-19, Wang et al (2022) concluded that parental involvement had a positive impact on children's achievement in Chinese and English, but not in math. While parents are likely to be knowledgeable about the learning content of Chinese and English lessons, this may not be the case for math lessons.…”
Section: Methodsmentioning
confidence: 99%
“…Teachers' readiness in the literacy teaching process also includes an orientation to incorporating parents in literacy learning, particularly in forming reading habits. The involvement of parents plays a vital role in the success of student learning (Alharthi, 2023;Rousoulioti et al, 2022;Wang et al, 2023), especially when it comes to gaining English literacy (Mak et al, 2023;Padmadewi et al, 2018). As a result, teachers are encouraged to employ parental involvement in learning English literacy in schools, particularly for elementary school students who still require parental guidance and supervision.…”
Section: Discussionmentioning
confidence: 99%
“…This study aims to fill this gap by developing and validating a quantitative scale that assesses technology integration in primary mathematics education based on seven critical factors: Attitude, AI Utilization (AIU), Contextual Factors (CF), Technological Pedagogical Knowledge and Technological Content Knowledge (TPK_TCK), Technological Pedagogical and Content Knowledge (TPACK), Educational Challenges (EC), and Parental and Community Involvement (PCI). These factors have been identified through a rigorous review of relevant theories and empirical studies and are deemed essential for a holistic understanding of technology integration in this context (Davis, 1989;Ertmer et al, 2014;Mishra & Koehler, 2006;Wang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…EC refers to the barriers and difficulties in integrating technology into primary mathematics classrooms (Ertmer et al, 2014). Finally, PCI recognizes the crucial role played by parents and the community in supporting and enabling technology integration in schools (Wang et al, 2023). Based on the seven dimensions, this study aims to develop a scale to offer educators and researchers a reliable and valid instrument to measure the complex dimensions of technology integration in primary mathematics education.…”
Section: Introductionmentioning
confidence: 99%